Validation of the Instrument of Organizational Commitment in Mexico: Evidence of construct validity, criterion validity and reliability - Fonseca Herrera, Jessica M. G. (2018)
The aim of this study was to provide evidence of construct validity, criterion validity, and internal consistency of an instrument that measures organizational commitment. First, an exercise with natural semantic networks was developed to get a pool of items, which were subsequently validated by judges. The second study was a first test of the instrument with 40 items, in a sample of 140 workers of a public university in the state of Guanajuato, Mexico. The results of the second study identify four factors with adequate levels of reliability. For the third study, the final instrument composed of 25 items was answered by 230 workers of a second public university, identifying three factors (affective, moral and identification with goals and values) with reliability indexes of ? of .86 to .89. These factors are theoretically consistent. We discuss possible uses, scope and limitations of the final instrument.